2014
DOI: 10.1021/jp5083449
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Templated CeO2 as Active Material for Thermochemical CO Production

Abstract: Heterogeneous reactions benefit from active materials with accessible pores and high surface areas. Such materials can be synthesized, for example, by templating methods. Particularly high surface areas are obtained in nanoporous solids. However, the solid walls surrounding nanopores also have typical dimensions in the nanometer range, and these walls are prone to sintering at high temperatures, reducing the active surface area. Here we demonstrate wood templating as an approach that balances accessible porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
(116 reference statements)
2
32
1
Order By: Relevance
“…We have demonstrated the technical feasibility of the ceria‐based redox cycle using a solar cavity receiver containing porous structures and the entire production chain to solar kerosene from H 2 O and CO 2 . It was shown that the morphology of the porous structure has a significant impact on the cycle's performance, e.g., on the molar conversion and energy efficiency, because the reduction step is heat transfer controlled, while the oxidation step is surface/mass transfer controlled . Therefore, for a given volume of the solar cavity receiver, a desired porous structure should feature high mass loading for maximum fuel output, appropriate optical thickness for volumetric absorption and uniform heating during the endothermic reduction step, and a high specific surface area for rapid reaction kinetics during the exothermic oxidation step with H 2 O and/or CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated the technical feasibility of the ceria‐based redox cycle using a solar cavity receiver containing porous structures and the entire production chain to solar kerosene from H 2 O and CO 2 . It was shown that the morphology of the porous structure has a significant impact on the cycle's performance, e.g., on the molar conversion and energy efficiency, because the reduction step is heat transfer controlled, while the oxidation step is surface/mass transfer controlled . Therefore, for a given volume of the solar cavity receiver, a desired porous structure should feature high mass loading for maximum fuel output, appropriate optical thickness for volumetric absorption and uniform heating during the endothermic reduction step, and a high specific surface area for rapid reaction kinetics during the exothermic oxidation step with H 2 O and/or CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[16] It was shown that the morphology of the porous structure has a significant impact on the cycle's performance, e.g., on the molar conversion and energy efficiency, because the reduction step is heat transfer controlled, while the oxidation step is surface/mass transfer controlled. [13,17,18] Therefore, for a given volume of the solar cavity receiver, a desired porous structure should feature high mass loading for maximum fuel output, appropriate optical thickness for volumetric absorption and uniform heating during the endothermic reduction step, and a high specific surface area for rapid reaction kinetics during the exothermic oxidation step with H 2 O and/or CO 2 . Reticulated porous ceramic (RPC) foam-type structures with dual-scale interconnected porosity (mm-and μm-sized pores within the struts) fulfill some of these desired characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the geometrical concentration ratio is defined (Malonzo et al, 2014), which correspond to the ratio between the collector area and the receiver area. However, this definition assumes a perfect energy conversion efficiency during the redirection and concentration steps.…”
Section: Definitionsmentioning
confidence: 99%
“…This field has recently picked up momentum driven by the desire for alternative, renewable and sustainable approaches for fuel processing, and material and chemical commodity production, as well as for direct, energydense, and long-term storage of solar energy. Among the existing solar-driven, non-biological chemistry routes which include solar thermochemistry, photocatalysis and photoelectrochemistry, solar thermochemistry has reached the largest scale demonstrations (up to 100 kW) (Villasmil et al, 2013;Chueh et al, 2010;Säck et al, 2016), demonstrated stability over hundreds of cycles (Malonzo et al, 2014), and enormous versatility in demonstrated chemical reactions (Scheffe and Steinfeld, 2014;Steinfeld, May 2005;Romero and Steinfeld, 2012;Bader and Lipinski, 2017).…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation